2004
DOI: 10.1021/la035334r
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Conductivity and Viscosity Measurements as a Technique To Track Emulsion Inversion by the Phase-Inversion-Temperature Method

Abstract: Two kinds of transitions can occur when an emulsified water-oil-ethoxylated nonionic surfactant system is cooled under constant stirring. At a water-oil ratio close to unity, a transitional inversion takes place from a water-in-oil (W/O) to an oil-in-water (O/W) morphology according to the so-called phase-inversion-temperature method. At a high water content, a multiple w/O/W emulsion changes to a simple O/W emulsion. The continuous monitoring of both the emulsion conductivity and viscosity allows the identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
79
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(86 citation statements)
references
References 53 publications
4
79
0
3
Order By: Relevance
“…3, both emulsification courses were near the inversion point, the boundary between S + O and W m + O, which was located at a ratio of aqueous phase to Tween20 of 3.5:6.5. Around the transition point, surfactant hydrophilic-lipophilic properties are balanced, the interfacial tension decreases, and thus tend to produce highly viscous emulsions with smaller droplet sizes (Allouche et al, 2004;Solans and Solè, 2012). In this study, there was no obvious phase behavior difference between the water and sucrose solution/Tween20/vegetable oil systems, except for the minimal difference in the boundary between the W m and S phases.…”
Section: The Preparation Of Nano-emulsions Using Low-energy Methodsmentioning
confidence: 54%
“…3, both emulsification courses were near the inversion point, the boundary between S + O and W m + O, which was located at a ratio of aqueous phase to Tween20 of 3.5:6.5. Around the transition point, surfactant hydrophilic-lipophilic properties are balanced, the interfacial tension decreases, and thus tend to produce highly viscous emulsions with smaller droplet sizes (Allouche et al, 2004;Solans and Solè, 2012). In this study, there was no obvious phase behavior difference between the water and sucrose solution/Tween20/vegetable oil systems, except for the minimal difference in the boundary between the W m and S phases.…”
Section: The Preparation Of Nano-emulsions Using Low-energy Methodsmentioning
confidence: 54%
“…This phenomenon might be attributed to the incomplete phase inversion of the emulsion. Phase inversion merely occurred in the location where the f w is higher than the average f w of the emulsion or the location where the temperature was lower than the average temperature of the system caused by fluctuations, and the O/W part dispersed in water while the W/O part floated on the water . When the emulsion was cooled further, the conductivity tended to be constant after a small drop and the viscosity tended to be constant, meanwhile, the W/O part disappeared and the emulsion could be fully dispersed in water, which demonstrated that complete phase inversion was achieved.…”
Section: Resultsmentioning
confidence: 99%
“…There are two main viewpoints to explain the driving force of phase inversion, namely the thermodynamic theory and hydrodynamic theory. According to the thermodynamic theory, the phase inversion of SOW systems essentially depends on the relative affinity of the surfactant for the oil and water phase, which is triggered due to the change of the hydrophilic‐lipophilic deviation (HLD) of surfactant, and the curvature of the oil‐water interface determines the type of the emulsion. When HLD > 0, the surfactant exhibits a stronger affinity for oil and the emulsion morphology tends to be W/O.…”
Section: Introductionmentioning
confidence: 99%
“…Other reports in the literature (Allouche et al 2004) show that the smaller the particle size of an emulsion, the higher it's the viscosity. Therefore, the behavior of the w=o emulsions analyzed above regarding PIT is related to the quantity of oil: the higher the oil concentration, the larger the size of the droplets generated, and hence the lower the viscosity.…”
Section: Pit By Rheology and Microcalorimetry 2871mentioning
confidence: 94%